Coeliac disease and malignancy of the duodenum: diagnosis by endoscopy, successful treatment of the malignancy, and response to a gluten free diet. Issue 1 (January 1991) - Hall, M J; Cooper, B T; Rooney, N; Thompson, H; Read, A E
Abstract : A patient presented with subtotal villous atrophy and a malignant duodenal tumour of uncertain histogenesis. He was successfully treated by resection and chemotherapy and the small bowel mucosa recovered on a gluten free diet. The tumour was diagnosed at upper gastrointestinal endoscopy when barium studies and abdominal computed tomography were normal, thus making this one of the earliest coeliac malignancies diagnosed.